Body weight‐supported training in Becker and limb girdle 2I muscular dystrophy. Issue 2 (19th May 2016) - Jensen, Bente R.; Berthelsen, Martin P.; Husu, Edith; Christensen, Sofie B.; Prahm, Kira P.; Vissing, John
ABSTRACT: Introduction : We studied the functional effects of combined strength and aerobic anti‐gravity training in severely affected patients with Becker and Limb‐Girdle muscular dystrophies. Methods : Eight patients performed 10‐week progressive combined strength (squats, calf raises, lunges) and aerobic (walk/run, jogging in place or high knee‐lift) training 3 times/week in a lower‐body positive pressure environment. Closed‐kinetic‐chain leg muscle strength, isometric knee strength, rate of force development (RFD), and reaction time were evaluated. Results : Baseline data indicated an intact neural activation pattern but showed compromised muscle contractile properties. Training (compliance 91%) improved functional leg muscle strength. Squat series performance increased 30%, calf raises 45%, and lunges 23%. Conclusions : Anti‐gravity training improved closed‐kinetic‐chain leg muscle strength despite no changes in isometric knee extension strength and absolute RFD. The improved closed‐kinetic‐chain performance may relate to neural adaptation involving motor learning and/or improved muscle strength of other muscles than the weak knee extensors. Muscle Nerve 54 : 239–243, 2016